Interlayer Magnetic Interaction in the CrI3/CrSe2 Heterostructure - Wang, Qiu-Hao; Ni, Mei-Yan; Li, Shu-Jing; Zheng, Fa-Wei; Lu, Hong-Yan; Zhang, Ping (Chinese physics letters, 2024)
Based on first-principles calculations,we systematically study the stacking energy and interlayer magnetic interaction of the heterobilayer composed of CrI3 and CrSe2 monolayers.It is found that the stacking order plays a crucial role in the interlayer magnetic coupling.Among all possible stacking structures,the AA-stacking is the most stable heterostructure,exhibiting interlayer antiferromagnetic interactions.Interestingly,the interlayer magnetic interaction can be effectively tuned by biaxial strain.A 4.3％compressive strain would result in a ferromagnetic interlayer interaction in all stacking orders.These results reveal the magnetic properties of CrI3/CrSe2 heterostructure,which is expected to be applied to spintronic devices.